Poetry on Visual Arts - Rajbhandari, Jitendra Man (SIRJANĀ – A Journal Of Arts and Art Education, 2016)
The affinity between a literary work and a visual art has long been a favourite issue for academic discourse among scholars, critics and philosophers alike. Both a work of literature and a visual art, being the powerful modes of human expression, represent biased or unbiased perception of their creators.